2017
DOI: 10.1093/scan/nsx012
|View full text |Cite
|
Sign up to set email alerts
|

Tolerating dissimilar other when primed with death: neural evidence of self-control engaged by interdependent people in Japan

Abstract: Mortality salience (MS) has been shown to lead to derogation of others with dissimilar worldviews, yet recent research has shown that Asian-Americans who presumably adopt an interdependent self-construal (SC) tend to reveal greater tolerance after MS induction. In the present study, we demonstrated that Japanese individuals who are high on interdependent SC indeed show greater tolerance toward worldview-threatening other in the MS (vs control) condition, thus replicating the prior research. Extending this rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Although the assessments of cultural worldview defense often include criticism the person who does not share the cultural worldview with the participant, criticism may be inconsistent with the cultural context for those who live in an interdependent culture. Indeed, Yanagisawa et al (2017) demonstrated that highly interdependent participants evaluate an anti-Japan essay writer more positively, rather than negatively, in the MS condition than in the control condition. But this explanation may be not applicable to our results because the participants evaluated the anti-Japan essay writer more negatively than neutral essay writer (the main effect of essay).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the assessments of cultural worldview defense often include criticism the person who does not share the cultural worldview with the participant, criticism may be inconsistent with the cultural context for those who live in an interdependent culture. Indeed, Yanagisawa et al (2017) demonstrated that highly interdependent participants evaluate an anti-Japan essay writer more positively, rather than negatively, in the MS condition than in the control condition. But this explanation may be not applicable to our results because the participants evaluated the anti-Japan essay writer more negatively than neutral essay writer (the main effect of essay).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, they found that when mortality was salient, positive evaluations of the sports essay increased and evaluations of the anti-Japan essay did not change. Subsequent studies by Yanagisawa and colleagues also reported no main effects of MS on cultural worldview defense (Yanagisawa et al, 2016(Yanagisawa et al, , 2017. 2 Toya and Nakashima (2017) also investigated whether Japanese people in their 20s and 50s react with cultural worldview defense in the MS condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural psychologists have discovered that while independent self-construal is predominant in Western societies, interdependent selfconstrual emphasizing harmonious relationships with others is common in Eastern societies [9]. Previous research pointed out that this difference could in uence a worldview defense effect among the Japanese [10]. TMT posits that MS motivates individuals to adapt to the criteria of their worldviews.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it can be assumed that when mortality is salient, people with interdependent self-construal will exhibit tolerance of others, even when the target has insulted their worldviews. Indeed, Yanagisawa et al [10] found that individuals with highly interdependent self-construal tended to evaluate those who wrote anti-Japanese essays more positively after MS priming. Importantly, their neurophysiological analysis indicated that individuals with highly interdependent self-construal attempted to exercise self-control and behave in a socially acceptable manner when faced with MS.…”
Section: Introductionmentioning
confidence: 99%